Opioid guidelines for common dental surgical procedures: a multidisciplinary panel consensus. Issue 3 (March 2020) - Farooqi, O.A.; Bruhn, W.E.; Lecholop, M.K.; Velasquez-Plata, D.; Maloney, J.G.; Rizwi, S.; Templeton, R.B.; Goerig, A.; Hezkial, C.; Novince, C.M.; Zieman, M.T.; Lotesto, A.M.N.; et al.
Abstract: One in 16 patients prescribed opioids after a surgical procedure will become a long-term user. The lack of procedure-specific guidelines after common dental procedures contributes to the opioid overprescribing problem. We convened a multidisciplinary panel to develop consensus recommendations for opioid prescribing after common dental procedures. We used a three-step modified Delphi method to develop a consensus recommendation for outpatient opioid prescribing for 14 common dental procedures. The multi-institution, multidisciplinary panel represented seven relevant stakeholder groups (oral surgeons, periodontists, endodontists, general dentists, general surgeons, oral surgery residents, and oral surgery patients). The panel determined the minimum and maximum number of opioid tablets a clinician should consider prescribing. For all 14 surgical procedures, ibuprofen was recommended as initial therapy. The maximum number of opioid tablets recommended varied by procedure (overall median = 5 tablets, range = 0–15 tablets). Zero opioid tablets were recommended as the maximum number for six of 14 (43%) procedures, one to 10 opioid tablets was the maximum for four of 14 (27%) procedures, and 11–15 tablets was the maximum for four of 14 (27%) procedures. Procedure-specific prescribing recommendations may help provide guidance to clinicians and help address the opioid overprescribing problem.